Using economic policy to improve environmental protection in Pakistan - Faruqee, Rashid; World Bank. (Washington, D.C. : World Bank, South Asia, Country Dept. I, Agriculture and National Resources Division, 1997)
The author studies Pakistan's major environmental problems, both green and brown, and assesses the extent to which economic policies affect incentives to protect the environment.
"April 1997"--Cover.
Paper presented at the Annual General Meeting of the Pakistan Institute of Development Economics, December 13-15, 1996, Islamabad.
Includes bibliographical references: p. 22-23.
aia 22/09/2016
Loans
Keywords: Environmental protection; Pakistan